KINERJA BERKELANJUTAN UMKM DI BALI: PERAN LITERASI KEUANGAN INOVASI FINTECH DAN INKLUSI KEUANGAN - I Gusti Ngurah Agung Kepakisan Mandala; Putu Yudha Asteria Putri (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the creative industry sector tend to be oriented towards short-term business decisions, which causes stagnation and lack of direction in long-term development. Lack of access to structured information on finance, market share, and business management is a major challenge for MSMEs. Bali is one of the provinces with a large number of MSMEs and has the potential to improve the Indonesian economy. This study aims to analyze the effect of financial literacy, fintech innovation, and financial inclusion on the sustainable performance of MSMEs in Bali. The research method uses a quantitative approach with financial literacy, fintech innovation, and financial inclusion as independent variables and sustainable performance of MSMEs as the dependent variable. Data were collected by distributing questionnaires to 100 MSMEs and analyzed using a structural equation model based on Partial Least Square (PLS). The results of this study are expected to provide insight for stakeholders in designing more effective policies to improve the competitiveness and sustainability of MSMEs through increasing financial literacy, utilizing financial technology, and expanding access to formal financial services.